Update Breast Cancer 2019 Part 4 – Diagnostic and Therapeutic Challenges of New, Personalised Therapies for Patients with Early Breast Cancer - Schütz, Florian; Fasching, Peter A.; Welslau, Manfred; Hartkopf, Andreas D.; Wöckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Lüftner, Diana; Belleville, Erik; Kolberg, Hans-Christian; Overkamp, Friedrich; Taran, Florin-Andrei; Brucker, Sara Y.; Wallwiener, Markus; Tesch, Hans; Fehm, Tanja N.; Schneeweiss, Andreas; Müller, Volkmar (Geburtshilfe und Frauenheilkunde, 2019)
The further development of therapies for women with early breast cancer is progressing far more slowly than in the case of patients with advanced breast cancer and is additionally delayed compared to developments in metastatic breast cancer. Nonetheless, significant advancements have been able to be recorded recently. This review summarises the latest developments in view of the most recent publications and professional conferences. For hormone-receptor-positive patients, new aspects for the duration of antihormone therapy and with regard to the benefits of multigene tests have been published. In the case of HER2-positive patients, the value of post-neoadjuvant therapy and de-escalation of the therapy is discussed. In patients with triple-negative breast cancer, there is a question of whether the knowledge of the biological background of a homologous recombination deficiency (HRD) helps develop new therapies for this subtype. In particular the “use” of a BRCA1/2 mutation or the biological characteristic HRD as a potential motive for therapy plays a role here in specifying the significance of platinum therapy and therapy with PARP inhibitors.Die Weiterentwicklung der Therapien für Frauen mit einem frühen Mammakarzinom schreitet deutlich langsamer voran als bei Patientinnen mit fortgeschrittenem Mammakarzinom und ist zudem zeitlich versetzt zu Entwicklungen beim metastasiertem Mammakarzinom. Trotzdem konnten in letzter Zeit deutliche Fortschritte verzeichnet werden. Diese Übersichtsarbeit fasst die jüngsten Entwicklungen vor dem Hintergrund der neuesten Publikationen und Fachkongresse zusammen. Für hormonrezeptorpositive Patientinnen sind neue Aspekte für die Dauer der Antihormontherapie und in Bezug auf den Nutzen von Multigentests veröffentlicht worden. Bei HER2-positiven Patientinnen wird der Stellenwert einer post-neoadjuvanten Therapie und eine Deeskalation der Therapie diskutiert. Bei Patientinnen mit tripel-negativem Mammakarzinom stellt sich die Frage, ob das Wissen um den biologischen Hintergrund einer Defizienz der homologen Rekombination (HRD) dabei hilft, neue Therapien für diesen Subtyp zu entwickeln. Insbesondere die „Nutzung“ einer BRCA1/2-Mutation oder des biologischen Merkmals HRD als potenzielles Therapiemotiv spielen dabei eine Rolle, den Stellenwert der Platintherapie und einer Therapie mit PARP-Inhibitoren zu spezifizieren.
Keywords: breast cancer; adjuvant; neoadjuvant; chemotherapy; antihormone therapy; multigene tests